2006
DOI: 10.1159/000095425
|View full text |Cite
|
Sign up to set email alerts
|

Management of Acute Severe Hyperlipidemic Pancreatitis

Abstract: Background/Aim: Hypertriglyceridemia is rare and can provoke acute severe hyperlipidemic pancreatitis when triglyceride levels exceed 11.3 mmol/l. In 10 patients we evaluated the therapeutic guidelines for severe hyperlipidemic pancreatitis. Methods: Ten patients (8 men and 2 women) were admitted to the intensive care unit with a diagnosis of acute severe hyperlipidemic pancreatitis. They underwent standard treatment. Heparin, insulin and antihyperlipidemic drugs were used to lower the triglyceride levels. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 52 publications
4
70
0
4
Order By: Relevance
“…Several reports [25][26][27][28][29] document the successful use of TPE in treatment of hypertriglyceridemia. In some instances, TPE for hypertriglyceridemic pancreatitis resulted in improvements in clinical and laboratory findings and patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports [25][26][27][28][29] document the successful use of TPE in treatment of hypertriglyceridemia. In some instances, TPE for hypertriglyceridemic pancreatitis resulted in improvements in clinical and laboratory findings and patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Early plasmapheresis or lipid apheresis can effectively reduce serum triglyceride, inhibit disease progression, and prevent the recurrence of hyperlipidemic pancreatitis, but it has risk of acute coronary events. [10,11] Batashki et al [12] reported that intubation with artifi cial pulmonary ventilation and high volume continuous veno-venous hemofiltration (HV CVVH) should be performed because of the development of polyorgan insuffi ciency and ARDS. In our case, signs and symptoms of ARF were greatly improved after NPPV and conventional therapies, thus creating the opportunity to perform caesarean delivery when fetal distress occurred.…”
Section: Discussionmentioning
confidence: 99%
“…• Signs and symptoms of hyperlipidemia Hyperlipidemia usually has no noticeable symptoms and tends to be discovered during routine examination or evaluation for atherosclerotic CVD [19]. Commonly found are Xanthoma, Xanthelasma of the eyelid, Chest Pain, Abdominal Pain, Enlarged Spleen, Liver Enlarged, High cholesterol or TG levels, Heart attacks, a Higher rate of obesity and glucose intolerance, Pimple like lesions across the body, Atheromatous plaques in the arteries, Arcussenilis, Xanthomata [20].…”
Section: B) Secondary Hyperlipidemiamentioning
confidence: 99%